Fuzzy and Classical MCDM Techniques to Rank the Slope Stabilization Methods in a Rock-Fill Reservoir Dam - Sina Shafiee Haghshenas; Reza Mikaeil; Sami Shaffiee Haghshenas; Masoud Zare Naghadehi; Pedram Sirati Moghadam (Salehan Institute of Higher Education, 2017)
Slope stabilization is one of the most crucial tasks in rock-fill reservoir dam projects to prevention of erosion and destruction of upstream and downstream slopes. Inappropriate choice and design of the protection can cause irreparable damages imposing additional costs and time to the project. In this paper, the body slope ranking is conducted by using the classical and fuzzy multi-criteria decision making approaches specifically VIKOR and Fuzzy-TOPSIS methods. To this aim, eight important and effective criteria were considered to select the most appropriate cover among five most common ones for protecting and conserving body slope of the rock-fill dams. The study was conducted on a dam in Bijar city located in the province of Guilan, the north of Iran. According to results of a comparative analysis using fuzzy and classical MCDM techniques, the concrete facing cover and the soil-cement cover have placed at the highest and lowest ranks to protect the body of the dam, respectively, suggested by both employed methods.